Estimating carbon sequestration of Gigantochloa albociliata for carbon farming strategy - Abd Rahim, Nurul Husna; Amir, Atikah Fukaihah (2025)
This research explores the carbon sequestration potential of Gigantochloa albociliata (common name: buluh madu), positioning it as a viable option for both carbon farming and eco-friendly construction. Known for its rapid growth, extensive biomass accumulation, and structural durability, bamboo captures atmospheric CO2 efficiently, while also catering to the rising demand for sustainable construction materials. The study examines the economic viability and market interest in Gigantochloa albociliata, while also investigating its potential for carbon sequestration in underutilized spaces like road reserves. Through a combination of market analysis through narrative literature review, and experimental research, the study estimates the species’ carbon storage capacity, providing the dual benefits of improving landscape aesthetics and mitigating greenhouse gas emissions. Findings suggest that integrating Gigantochloa albociliata into sustainable land use and carbon offset initiatives could play a pivotal role in climate mitigation, delivering carbon credits, and fostering ecological resilience and biodiversity. Overall, this research highlights the potential of bamboo as a resource for sustainable development, contributing to global climate goals and offering socio-economic benefits in construction and agriculture.